Testing the law of one price in retail banking: An analysis for Colombia using a pair-wise approach (2013)
We apply a pair-wise approach to test the law of one price for deposit (lending) rates in Colombia. We find that when banks are of different sizes, deposit rates adjust quickly, suggesting a competitive environment. By contrast, lending rates adjust rapidly when banks are of similar sizes, supporting market segmentation. © 2012 Elsevier B.V.